Solid electrolyte, and electrode mixture, solid electrolyte layer, and solid battery using the same

A solid electrolyte with a high argyrodite crystal structure and controlled lattice strain enhances lithium ion conductivity, addressing the conductivity limitations in existing technologies by optimizing composition and manufacturing processes.

JP7601784B2Active Publication Date: 2024-12-17MITSUI MINING & SMELTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021553458
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-29
Filing Date
2020-10-20
Publication Date
2024-12-17
Estimated Expiration
2040-10-20

AI Technical Summary

Technical Problem

Existing solid electrolytes do not provide a specific method to increase lithium ion conductivity, and other factors for enhancing conductivity are not adequately addressed.

Method used

A solid electrolyte with a high argyrodite crystal structure ratio and controlled lattice strain is developed, comprising Li a P.S. b X c, where a is 3.0 to 6.0, b is 3.5 to 4.8, and c is 0.1 to 3.0, with a preferred argyrodite ratio of 97 wt% or more and lattice strain less than 0.10%, achieved through controlled synthesis and pulverization processes.

Benefits of technology

The electrolyte exhibits lithium ion conductivity of 4.0 mS/cm or more, significantly improving conductivity by optimizing the argyrodite fraction and reducing lattice strain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601784000001
    Figure 0007601784000001
Patent Text Reader

Abstract

A solid electrolyte according to the present invention contains a compound which contains a crystal phase having an argyrodite crystal structure, and which is represented by LiaPSbXc (wherein X represents at least one halogen element; a represents a number from 3.0 to 6.0; b represents a number from 3.5 to 4.8; and c represents a number from 0.1 to 3.0). The ratio of the crystal phase having an argyrodite crystal structure relative to all crystal phases constituting this solid electrolyte is 97.0 wt% or more. The compound has a lattice strain of less than 0.10%. It is preferable that this solid electrolyte has a lithium ion conductivity of 4.0 mS / cm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte, and an electrode mixture, a solid electrolyte layer, and a solid-state battery using the same. [Background technology]

[0002] In recent years, solid electrolytes have been attracting attention as an alternative to the electrolytes used in many liquid batteries. Solid-state batteries using such solid electrolytes are expected to be put to practical use as batteries that are safer than liquid batteries that use flammable organic solvents, and also have a high energy density.

[0003] As conventional techniques related to solid electrolytes, those described in Patent Documents 1 and 2 are known, for example. Patent Document 1 describes a solid electrolyte having the composition formula Li 7-x P.S. 6-x Ha x (Ha represents Cl or Br), and has a crystal structure that is a cubic crystal and belongs to the space group F-43m. 7-x-2y P.S. 6-x-y Cl x A sulfide solid electrolyte containing a compound represented by the formula: [Prior art documents] [Patent documents]

[0004] [Patent Document 1] US2016 / 156064A1 [Patent Document 2] US2017 / 222257A1 Summary of the Invention

[0005] High lithium ion conductivity is one of the properties required for a solid electrolyte. In order to increase the lithium ion conductivity, for example, it is considered to control the argyrodite ratio high in the techniques described in the above-mentioned Patent Documents 1 and 2. However, these documents do not disclose a specific method for increasing the argyrodite ratio. Furthermore, these documents do not particularly mention other factors for increasing the lithium ion conductivity. Therefore, an object of the present invention is to provide a solid electrolyte having high lithium ion conductivity.

[0006] The present invention relates to a crystalline phase having an argyrodite-type crystal structure, a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less), The ratio of a crystalline phase having an argyrodite-type crystal structure to the total crystalline phase constituting the solid electrolyte is 97 wt% or more, The present invention provides a solid electrolyte in which the lattice distortion of the compound is less than 0.10%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention will be described below based on its preferred embodiments. a P.S. b X c (X is at least one halogen element. a is a number between 3.0 and 6.0. b is a number between 3.5 and 4.8. c is a number between 0.1 and 3.0.) This compound includes a crystal phase having an argyrodite crystal structure. This compound is solid at room temperature (25°C) and has lithium ion conductivity. In the following description, this compound will be referred to as "compound A" for convenience.

[0008] Compound A in the present invention is a crystalline material containing a crystal phase having an argyrodite-type crystal structure. However, compound A may contain a glass component, i.e., an amorphous component. Compound A "containing a crystal phase having an argyrodite-type crystal structure" means that compound A needs to contain at least a crystal phase having an argyrodite-type crystal structure, and may contain a crystal phase (also referred to as a "heterogeneous phase") different from the crystal phase having the argyrodite-type crystal structure. Of course, compound A does not have to contain the heterogeneous phase.

[0009] Having a crystal phase with an argyrodite-type structure means having a crystal phase possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. It is particularly preferable that the compound having a crystal phase with an argyrodite-type structure has a crystal structure belonging to a cubic system from the viewpoint of improving lithium ion conductivity.

[0010] Whether or not the solid electrolyte of the present invention contains a compound having a crystal phase of an argyrodite structure can be confirmed by, for example, XRD measurement. That is, in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation, the crystal phase of the argyrodite structure has characteristic peaks at 2θ=15.34°±1.00°, 17.74°±1.00°, 25.19°±1.00°, 29.62°±1.00°, 30.97°±1.00°, 44.37°±1.00°, 47.22°±1.00°, and 51.70°±1.00°. Furthermore, for example, there are characteristic peaks at 2θ=54.26°±1.00°, 58.35°±1.00°, 60.72°±1.00°, 61.50°±1.00°, 70.46°±1.00°, and 72.61°±1.00°. In this specification, the term "peak" means the apex of a peak. In addition, it is preferable that the above peaks do not overlap with other peaks and exist independently.

[0011] In the solid electrolyte of the present invention, the crystal phase having an argyrodite-type crystal structure constituting compound A preferably constitutes a major phase with respect to all crystal phases. The major phase refers to the crystal phase that is present in the highest proportion, based on the number of moles, of all crystal phases in the solid electrolyte of the present invention. The solid electrolyte of the present invention may be composed only of a crystal phase having an argyrodite-type crystal structure, or may further contain a substance of a different phase from the crystal phase having an argyrodite-type crystal structure, so long as the effect of the present invention is not impaired. Examples of such a substance of a different phase include lithium halide and Li3PS4.

[0012] As described above, the solid electrolyte of the present invention contains compound A including a crystal phase having an argyrodite-type crystal structure, and the solid electrolyte may further include a phase different from the crystal phase having the argyrodite-type crystal structure. One of the features of the solid electrolyte of the present invention is that the argyrodite ratio in the solid electrolyte is controlled. The argyrodite ratio refers to the mass ratio (wt%) of the crystal phase having the argyrodite structure to the total crystal phase constituting the solid electrolyte of the present invention. Another feature of the solid electrolyte of the present invention is that the lattice distortion of compound A contained in the solid electrolyte is controlled.

[0013] In detail, the solid electrolyte of the present invention has a high argyrodite ratio and a small lattice distortion of compound A. This improves the lithium ion conductivity of the solid electrolyte of the present invention. The inventors believe that the reason for this is as follows.

[0014] The solid electrolyte of the present invention contains compound A. In a solid electrolyte containing compound A, it has been believed that the higher the proportion of a crystal phase having an Argyrodite type crystal structure, the higher the lithium ion conductivity of the solid electrolyte. However, it has not been possible to control the Argyrodite ratio in the solid electrolyte to a high value. In response to this, the present inventor has found that the Argyrodite ratio of the solid electrolyte can be controlled to a high value by producing the solid electrolyte by the method described below. Furthermore, the present inventor has found that the lithium ion conductivity of the solid electrolyte can be further increased not only by increasing the Argyrodite ratio of the solid electrolyte but also by controlling the lattice distortion of compound A to a small value. Small lattice distortion means that atoms are present in the appropriate positions in the crystal structure of compound A. It is believed that this makes it easier for lithium ions to be smoothly conducted through compound A, thereby improving the lithium ion conductivity of the solid electrolyte.

[0015] In order to make the above-mentioned advantageous effects more pronounced, the ratio of the crystal phase having an argyrodite-type crystal structure to all the crystal phases constituting the solid electrolyte (hereinafter sometimes simply referred to as the "argyrodite ratio") is, for example, preferably 97.0 wt% or more, more preferably 97.2 wt% or more, and even more preferably 97.4 wt% or more. The higher the argyrodite ratio, the more preferable, and ideally 100 wt%. The upper limit of the argyrodite ratio that can be achieved with the current technological level is about 98.6 wt%, and if the argyrodite ratio is this high, the lithium ion conductivity of the solid electrolyte will be sufficiently high.

[0016] From the same viewpoint as above, in the solid electrolyte of the present invention, the lattice distortion of the compound A contained in the solid electrolyte is preferably less than 0.10%, more preferably 0.09% or less, and even more preferably 0.08% or less. The smaller the lattice distortion of the compound A, the more preferable it is from the viewpoint of improving the lithium ion conductivity of the solid electrolyte. The lower limit of the lattice distortion that can be achieved with the current technical level is about 0.04%. By making the lattice distortion of the compound A smaller, the lithium ion conductivity of the solid electrolyte can be sufficiently increased.

[0017] A specific method for measuring the argyrodite ratio in the present invention will be described in detail in the Examples below. The lattice distortion of compound A contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. A specific method will be described in detail in the Examples below.

[0018] The solid electrolyte of the present invention exhibits a high lithium ion conductivity at room temperature (25° C.) of preferably 4.0 mS / cm or more, more preferably 4.5 mS / cm or more, even more preferably 4.8 mS / cm or more, and even more preferably 6.0 mS / cm or more, by controlling the Argyrodite ratio of the solid electrolyte and the lattice distortion of compound A. The lithium ion conductivity of the solid electrolyte can be measured by the method described in the examples below.

[0019] As described above, the compound A contained in the solid electrolyte of the present invention is Li a P.S. b X c Here, "compound A is Li a P.S. b X c "represented by" means that compound A is Li a P.S. b X cIn this composition formula, a, which indicates the molar ratio of lithium (Li), is preferably, for example, a number between 3.0 and 6.0, more preferably a number between 3.2 and 5.8, and even more preferably a number between 3.4 and 5.4. Note that a may be less than 5.4. In the composition formula, b, which indicates the molar ratio of sulfur (S), is preferably, for example, a number from 3.5 to 4.8, more preferably from 3.8 to 4.6, and even more preferably from 4.0 to 4.4. Note that b may be less than 4.4. Furthermore, in the composition formula, c is preferably, for example, a number of 0.1 or more and 3.0 or less, more preferably a number of 0.2 or more and 2.5 or less, and even more preferably a number of 0.4 or more and 2.0 or less. Compound A in which a, b, and c are within this range has sufficiently high lithium ion conductivity. In the composition formula, X represents at least one halogen element. When X is one type, compound A is Li a P.S. b F c , Li a P.S. b Cl c , Li a P.S. b Br c and Li a P.S. b I c When there are two types of X, compound A is Li a P.S. b X 1 y X 2 z It is expressed as X 1 and X 2 Each represents a different halogen element. Also, y and z represent numbers greater than 0 that satisfy c=y+z. X 1 and X 2 Examples of the combination of X include a combination of Cl and Br, a combination of Cl and I, and a combination of Br and I. When X is three types, compound A is Li a P.S. b X 1 yX 2 z X 3 v It is expressed as X 1 , X 2 and X 3 Each represents a halogen element that is different from the others. Also, y, z, and v represent numbers greater than 0 that satisfy c=y+z+v. X 1 and X 2 and X 3 An example of the combination is a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one type of the above-mentioned compound A, or may contain two or more types of compound A.

[0020] In the present invention, the amount of Li a P.S. b X c Compound A obtained in such a manner may contain elements other than lithium (Li), phosphorus (P), sulfur (S) and halogen (X). For example, it may be possible to replace a part of the lithium (Li) element with another alkali metal element, to replace a part of the phosphorus (P) element with another pnictogen element, or to replace a part of the sulfur (S) element with another chalcogen element.

[0021] The solid electrolyte of the present invention may contain, for example, impurities in addition to the compound A. From the viewpoint of low influence on performance, the content of the impurities can be, for example, less than 5 mol%, preferably less than 3 mol%, and particularly preferably less than 1 mol%.

[0022] When the solid electrolyte of the present invention contains only one type of compound A, it is preferable that the lattice distortion of the compound A satisfies the above-mentioned range. On the other hand, when the solid electrolyte of the present invention contains two or more types of compounds A, it is preferable that the lattice distortion of at least one type of compound A satisfies the above-mentioned range, and it is preferable that the lattice distortion of all compounds A satisfies the above-mentioned range.

[0023] From the viewpoint of suppressing viscosity during slurry preparation, the solid electrolyte of the present invention has a BET specific surface area of ​​12 m 2 / g or less, and 2 / g or less is more preferable, 2 From the viewpoint of suppressing the viscosity during slurry preparation, the smaller the BET specific surface area, the better. However, if it is too small, there is a concern that the lithium ion conductivity will decrease due to the decrease in the number of contact points. Therefore, the BET specific surface area is set to 1.0 m 2 / g or more, especially 1.5m 2 / g or more, especially 2.0m 2 / g, it is possible to sufficiently suppress the decrease in lithium ion conductivity due to the decrease in contact points, and it is also effective in suppressing the viscosity during slurry preparation. The BET specific surface area in this range can be achieved, for example, by controlling the particle size of the solid electrolyte. The method for measuring the BET specific surface area will be described in detail in the Examples below.

[0024] The solid electrolyte is composed of a powder as an aggregate of particles. The particle size of the solid electrolyte of the present invention is determined by a volume cumulative particle size D at 50% cumulative volume by a laser diffraction / scattering particle size distribution measurement method. 50 The volume cumulative particle diameter D is preferably 0.8 μm or more, more preferably 0.9 μm or more, and particularly preferably 1.0 μm or more. 50 The volume cumulative particle diameter D of the solid electrolyte of the present invention is preferably 15.0 μm or less, more preferably 10.0 μm or less, and particularly preferably 7.0 μm or less. 50 By having the upper limit, when the solid electrolyte of the present invention is used in combination with another solid electrolyte, the solid electrolyte of the present invention can easily enter the gaps of the other solid electrolyte. Due to this, the contact points and contact area between the solid electrolytes become large, and the lithium ion conductivity can be effectively improved. On the other hand, the volume cumulative particle diameter D of the solid electrolyte of the present invention is 50 By having the lower limit, it is possible to prevent the lattice distortion of compound A from becoming excessively large. In addition, it is possible to prevent the surface area of ​​the entire powder of the solid electrolyte from increasing, and to prevent problems such as an increase in resistance and difficulty in mixing with the active material.

[0025] The above mentioned D 50 In relation to the above, the solid electrolyte of the present invention has a volume cumulative particle size D at 10% by volume of cumulative volume measured by a laser diffraction scattering type particle size distribution measurement method. 10 is preferably 5.0 μm or less, more preferably 3.5 μm or less, and particularly preferably 2.0 μm or less. 10 For example, it is preferably 0.2 μm or more, more preferably 0.3 μm or more, and particularly preferably 0.4 μm or more. The solid electrolyte of the present invention has a volume cumulative particle size D at 95% by volume cumulative volume measured by a laser diffraction scattering type particle size distribution measurement method. 95 is preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. 95 For example, it is preferably 1.5 μm or more, more preferably 2.0 μm or more, and particularly preferably 2.5 μm or more. The volume cumulative particle size D 10 and D. 95 By setting the value of the above range, the lattice distortion of the compound A contained in the solid electrolyte can be sufficiently reduced, and an increase in the surface area of ​​the entire powder of the solid electrolyte can be suppressed, which makes it possible to further sufficiently increase the lithium ion conductivity of the solid electrolyte, which is preferable.

[0026] The solid electrolyte of the present invention can be preferably manufactured by the method described below. A lithium source compound, a phosphorus source compound, a sulfur source compound, and a halogen source compound are used as raw materials. For example, lithium sulfide (Li2S) can be used as the lithium source compound. For example, diphosphorus pentasulfide (P2S5) can be used as the phosphorus source compound. When the lithium source compound and / or the phosphorus source compound is a sulfide, the sulfide can be used as the sulfur source compound. For the halogen source compound, lithium halide can be used. These raw materials are mixed so that the lithium element, the phosphorus element, the sulfur element, and the halogen element are in a predetermined molar ratio. Then, the mixed raw materials are fired in an inert atmosphere or in an atmosphere containing hydrogen sulfide gas to obtain Li. a P.S. b X c Compound A having a crystal phase of an argyrodite structure is obtained. One example of a method for increasing the argyrodite ratio is to increase the reactivity between the raw materials during firing. Specifically, the raw materials, that is, the lithium source compound, the phosphorus source compound, the sulfur source compound, and the halogen source compound, are crushed to a desired particle size, the raw materials are mixed uniformly, and the raw materials are fired for a long period of time. The atmosphere containing hydrogen sulfide gas may be 100% hydrogen sulfide gas, or may be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. The firing temperature is preferably, for example, 350°C or higher and 550°C or lower. The holding time at this temperature is preferably, for example, 0.5 hours or higher and 20 hours or lower.

[0027] A solid electrolyte containing compound A is obtained by the above-mentioned method. At this point, the crystallinity of compound A contained in the solid electrolyte is high and the lattice distortion is low. However, since the particle size is not the desired value, it is necessary to adjust the particle size. To achieve this, the solid electrolyte needs to be pulverized, but the pulverization may cause lattice distortion in compound A. Therefore, the inventors have found that it is advantageous to subject the solid electrolyte to pulverization under conditions that do not increase the lattice distortion.

[0028] The pulverization process can be performed by a wet or dry method. In order to prevent the lattice distortion from increasing, it is desirable to reduce the pulverization energy during the pulverization process. Specifically, the weight and / or number of the dispersion media can be reduced, and the peripheral speed and / or processing time can be reduced. However, the method for preventing the lattice distortion from increasing is not limited to these. Various media mills can be used for the pulverization process. As the media mill, a ball mill, a bead mill, a paint shaker, a homogenizer, etc. can be used. As the dispersion media used in the media mill, balls and beads made of various ceramics including alumina and zirconia are used. The diameter of the dispersion media can be, for example, 0.1 mm or more and 50 mm or less.

[0029] When the grinding process is performed by a wet method, it is preferable to use an organic solvent as a dispersion medium, since it can suppress the generation of hydrogen sulfide caused by the reaction between the solid electrolyte and water. Examples of the organic solvent include aromatic organic solvents such as toluene, xylene, benzene, and solvent naphtha, and aliphatic organic solvents such as heptane, decane, normal hexane, cyclohexane, and mineral spirits. These organic solvents can be used alone or in combination of two or more.

[0030] The organic solvent and the solid electrolyte are mixed to form a slurry, and the slurry is subjected to wet pulverization. The concentration of the solid electrolyte contained in the slurry is preferably set to, for example, 5% by mass or more and 50% by mass or less, since the increase in lattice distortion of compound A is suppressed and a solid electrolyte with high lithium ion conductivity is easily obtained. In the wet pulverization using a media mill, the ratio of the dispersion medium to the slurry is preferably set to 5 parts by mass or more and 50 parts by mass or less for 100 parts by mass of the slurry, since the increase in lattice distortion of compound A can be suppressed. The dispersion time by the media mill is generally preferably set to 0.5 hours or more and 60 hours or less, since the increase in lattice distortion of compound A can be suppressed.

[0031] When wet grinding is performed, the volume cumulative particle size D of the solid electrolyte after wet grinding is 50 From the viewpoint of enhancing the lithium ion conductivity of the solid electrolyte, it is preferable to adjust the degree of pulverization so that the lattice distortion is not increased, so that the lattice distortion is preferably 0.8 μm or more, more preferably 0.9 μm or more, and even more preferably 1.0 μm or more.

[0032] The solid electrolyte of the present invention thus obtained can be used, for example, as a material constituting a solid electrolyte layer or a material contained in an electrode mixture containing an active material. Specifically, it can be used as a positive electrode mixture constituting a positive electrode layer containing a positive electrode active material, or as a negative electrode mixture constituting a negative electrode layer containing a negative electrode active material. Therefore, the solid electrolyte of the present invention can be used in a battery having a solid electrolyte layer, that is, a so-called solid battery. More specifically, it can be used in a lithium solid battery. The lithium solid battery may be a primary battery or a secondary battery, and is preferably used in a lithium secondary battery. The term "solid battery" includes not only a solid battery that does not contain any liquid or gel material as an electrolyte, but also an embodiment that contains, for example, 50% by mass or less, 30% by mass or less, or 10% by mass or less of a liquid or gel material as an electrolyte.

[0033] The solid electrolyte layer in the solid battery can be produced by, for example, dropping a slurry containing the solid electrolyte of the present invention, a binder and a solvent onto a substrate and scraping it off with a doctor blade or the like, contacting the substrate with the slurry and then cutting it with an air knife, forming a coating film by screen printing or the like and then removing the solvent by heating and drying, or the like. Alternatively, the solid electrolyte layer can be produced by press-molding the powder of the solid electrolyte of the present invention and then appropriately processing it. The solid electrolyte layer may contain other solid electrolytes in addition to the solid electrolyte of the present invention. The thickness of the solid electrolyte layer in the present invention is typically preferably 5 μm or more and 300 μm or less, more preferably 10 μm or more and 100 μm or less.

[0034] From the viewpoint of enhancing lithium ion conductivity, the solid electrolyte layer containing the solid electrolyte of the present invention preferably has a porosity of, for example, 50% or less, more preferably 30% or less, and even more preferably 20% or less. The porosity of the solid electrolyte layer can be adjusted, for example, by the pressing pressure when the powdered solid electrolyte of the present invention is made into a compact. The pressing pressure is preferably, for example, 20 MPa or more. The porosity can be calculated from the true density and apparent density of the solid electrolyte layer, which are determined by, for example, a liquid phase method (Archimedes method), using the following relational expression. Porosity (%) = (true density - apparent density) ÷ true density × 100

[0035] It is also possible to use a mixture of the solid electrolyte of the present invention and another solid electrolyte as the solid electrolyte layer. When the solid electrolyte of the present invention is mixed with another solid electrolyte, the solid electrolyte of the present invention can be used in combination with, for example, any of amorphous (glass), glass ceramics, and crystalline materials. When the other solid electrolyte to be mixed with the solid electrolyte of the present invention is a sulfide solid electrolyte, specific examples of the sulfide solid electrolyte include Li2S-P2S5, Li4P2S6, Li7P3S, and Li2S-P2S5. 11 The solid electrolyte to be combined may be a non-sulfide, for example, an oxide-based solid electrolyte.

[0036] The solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and it is preferable that the solid electrolyte layer contains the solid electrolyte of the present invention. Examples of the shape of the solid-state battery include a laminate type, a cylindrical type, and a square type.

[0037] The positive electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a positive electrode active material. As the positive electrode active material, for example, a material used as a positive electrode active material for a lithium secondary battery can be appropriately used. As the positive electrode active material, for example, a spinel-type lithium transition metal compound, a lithium metal oxide having a layered structure, etc. can be mentioned. In addition to the positive electrode active material, the positive electrode mixture may contain other materials such as a conductive assistant.

[0038] The negative electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a negative electrode active material. For example, a negative electrode mixture used as a negative electrode active material of a lithium secondary battery can be appropriately used as the negative electrode active material. For example, the negative electrode active material includes carbon materials such as lithium metal, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon), lithium titanate, titanium-niobium composite oxide, silicon, silicon compounds, tin, and tin compounds. In addition to the negative electrode active material, the negative electrode mixture may contain other materials such as a conductive assistant. EXAMPLES

[0039] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0040] Example 1 Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Li2S powder, P2S5 powder, LiCl powder, and LiBr powder were weighed out so as to obtain a composition of the above. These powders were pulverized and mixed using a ball mill to obtain a mixed powder. The mixed powder was fired to obtain a fired product made of lithium ion conductive sulfide. The firing was carried out using a tubular electric furnace. During the firing, hydrogen sulfide gas with a purity of 100% was circulated through the electric furnace at 1.0 L / min. The firing temperature was set at 450°C, and firing was carried out for 4 hours. XRD measurement revealed that the fired product contained a crystal phase with an argyrodite structure and LiCl. 0.5 Br 0.5 It was confirmed that the composition was as follows:

[0041] The fired material was roughly crushed with a mortar and pestle, then crushed with a hammer crusher, and the crushed material was mixed with a solvent to form a slurry with a concentration of 12% by mass. This slurry was subjected to wet grinding in a bead mill (zirconia beads with a diameter of 0.2 mm). Toluene was used as the solvent for the slurry. After wet grinding, the slurry was subjected to solid-liquid separation, and the solid content was dried. The dried fired material was sieved with a sieve with an opening of 53 μm to obtain the desired solid electrolyte.

[0042] Example 2 In Example 1, the firing temperature, pulverizing device, slurry concentration, and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0043] Example 3 The firing temperature and slurry concentration in Example 1 were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0044] Example 4 In Example 1, the firing temperature, pulverizing device, slurry concentration, and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0045] Comparative Example 1 In Example 1, the firing temperature, slurry concentration, and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0046] Comparative Example 2 In Example 1, the slurry concentration and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0047] [Rating 1] The argyrodite ratio of the solid electrolytes obtained in the examples and comparative examples was determined by the method described below. 5.4 P.S. 4.4 Cl 0.8 Br 0.8Furthermore, the lattice distortion of the solid electrolyte D 10 , D 50 and D. 95 The results are shown in Table 1 below.

[0048] [Measurement of Argyrodite Rate] A Rigaku SmartLab was used for the measurements. The optical system was focused, with a Johansson monochromator on the incident side and a D / teX Ultra 250 detector. A 5deg Soller slit was used for the incident and receiving parallel slits. A holder not exposed to air was used, the scanning axis was 2θ / θ, the scanning range was 20deg to 140deg, the step width was 0.01deg, and the scanning speed was set so that the maximum peak height was 10,000 counts or more. In addition, SRM660a (compound name: LaB6) manufactured by NIST (National Institute of Standards and Technology) was measured under the same conditions and used as a width standard. For the analysis, PDXL2 manufactured by Rigaku Corporation was used. The analysis procedure was as follows. First, identification was performed. The CIF file (Crystallographic Information File) described below was read and the substance was determined. The CIF file was obtained from ICSD (Inorganic Crystal Structure Database). For compound A, a CIF file with ICSD Collection Code 418490 was used, and for heterogeneous phases, for example, in the case of lithium halide, a CIF file with 53818 was used, and identification was performed with the appropriate CIF file until there were no unidentified peaks. Next, intensity decomposition was performed with WPPF. For width correction, the width standard data file was selected. This file corresponds to the file that was saved after the XRD data of SRM660a was identified with LaB6 and analyzed in the same manner as the analysis method described below. Quantitative values ​​were obtained from the analysis results, and the argyrodite ratio was calculated. [Analysis method] The peak angles and widths were corrected using an external standard sample. The "split Pearson VII function" was used as the model function for the peak shape. Next, from the "Basic" tab, "Refinement Parameter Settings" - "Method" was selected as "Intensity Decomposition". In addition, when lithium halide is included as a heterophase, the lattice constant changes depending on the state of halogenation, so the initial value of the lattice constant of the lithium halide was adjusted so that the XRD data and the calculated value roughly matched. Next, refinement was performed. In the refinement, various parameters were adjusted until sufficient convergence was achieved. For example, an S value of 1.5 or less is a good guideline.

[0049] [Measurement of lattice distortion] Measurement and analysis were carried out in the same manner as in [Measurement of Argyrodite Ratio], and the lattice distortion was calculated from the analysis results.

[0050] [D 10 , D 50 and D. 95 Measurement of Using an automatic sample feeder for laser diffraction particle size distribution measurement equipment (Microtrac SDC manufactured by Microtrac-Bell Corporation), the sample (powder) was put into an organic solvent, and after irradiating it with 30W ultrasonic waves for 60 seconds at a flow rate of 50%, the particle size distribution was measured using a laser diffraction particle size distribution measurement equipment (MT3000II manufactured by Microtrac-Bell Corporation), and the D was calculated from the obtained volumetric particle size distribution chart. 10 , D 50 and D. 95 The organic solvent used was toluene.

[0051] [Rating 2] The solid electrolytes obtained in the examples and comparative examples were measured for BET specific surface area and lithium ion conductivity by the methods described below. The results are shown in Table 1 below.

[0052] [Measurement of BET specific surface area] The sample (powder) was heated in a vacuum at 120°C for 1 hour using a pretreatment device, "BELPREP-vacII" manufactured by Microtrack-Bell Co., Ltd. After that, the specific surface area was calculated by the BET (Brunauer-Emmett-Teller) method from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a specific surface area measuring device, "BELSORP-miniII" manufactured by Microtrack-Bell Co., Ltd.

[0053] [Measurement of lithium ion conductivity] The solid electrolyte was uniaxially pressed in a glove box filled with sufficiently dried Ar gas (dew point -60°C or less). It was further pressed at 200 MPa using a cold isostatic pressing device to produce pellets with a diameter of 10 mm and a thickness of about 4 to 5 mm. Carbon paste was applied to the top and bottom surfaces of the pellet as electrodes, and then heat treatment was performed at 180°C for 30 minutes to produce a sample for ion conductivity measurement. The lithium ion conductivity of the sample was measured using a Solartron 1255B manufactured by Toyo Corporation. The measurement was performed by an AC impedance method under conditions of a temperature of 25°C and a frequency of 0.1 Hz to 1 MHz, while the molded sample was restrained with 6 Ncm.

[0054] [Table 1]

[0055] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples have higher lithium ion conductivity than the solid electrolytes of the comparative examples. [Industrial Applicability]

[0056] According to the present invention, a solid electrolyte having high lithium ion conductivity is provided.

Claims

1. It contains a crystal phase having an argyrodite type crystal structure, a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less), the ratio of a crystalline phase having an argyrodite-type crystal structure to the total crystalline phase constituting the solid electrolyte is 97 wt % or more; The compound has a lattice distortion of less than 0.10%, A solid electrolyte having a volume cumulative particle size D 50 of 7.0 μm or less at 50% cumulative volume, as measured by a laser diffraction / scattering particle size distribution measurement method.

2. 2. The solid electrolyte according to claim 1, having a lithium ion conductivity of 4.0 mS / cm or more.

3. The solid electrolyte according to claim 1, wherein the volume cumulative particle size D 10 at 10% of the cumulative volume measured by a laser diffraction scattering particle size distribution measurement method is 5.0 μm or less.

4. The solid electrolyte according to claim 1, wherein the volume cumulative particle size D 95 at 95% of the cumulative volume measured by a laser diffraction scattering particle size distribution measurement method is 40 μm or less.

5. An electrode mixture comprising the solid electrolyte according to claim 1 or 2 and an active material.

6. A solid electrolyte layer comprising the solid electrolyte according to claim 1 or 2.

7. A solid-state battery comprising the solid electrolyte according to claim 1 or 2.

Citation Information

Patent Citations

  • Sulfide solid electrolyte

    JP2018029058A

  • Sulfide-Based Solid Electrolyte for Lithium Ion Battery

    US20160156064A1

  • Sulfide-Based Solid Electrolyte for Lithium Ion Batteries

    US20170222257A1